MONROE BEARDSLEY AESTHETICS IN GUNONGAN ACEH ARCHITECTURE: A STUDY OF VALUE AND MEANING - Mursidiq, Mursidiq (Institut Seni Indonesia Padangpanjang, 2024)
This research discusses Gunongan Aceh, part of the 17th century royal palace complex, a historical relic of the time of Sultan Iskandar Muda. The research focuses on analyzing the aesthetics and meaning in the symmetrical architecture of Gunongan Aceh, which is rich in ornaments and decorative details. Qualitative research methods were used to deeply understand the structure and design of the building. Data collection techniques involved literature study, interviews, observation and documentation. Thematic and phenomenological analysis was applied to uncover the aesthetic aspects and symbolic meanings in the architecture. This research shows that analysis using Monroe Beardsley's aesthetic theory resulted in values and meanings relevant to Gunongan Aceh's architecture; Unity means the strong unity of the design reflects the harmony between the physical elements of the building, intensity means the historical and emotional meaning of this building as a symbol of the Sultan's love for his empress, and complexity means the richness of Aceh's nature and the cultural values contained in it. Thus, the relationship between Gunongan Aceh's architecture and Monroe Beardsley's aesthetic theory provides a solid foundation for understanding aesthetic value and meaning in the context of traditional Acehnese architecture.